Detecting Spatial Orientation Demand during Virtual Navigation using EEG Brain Sensing - Nguyen-Vo, Thinh; Riecke, Bernhard E. (Psychonomic Society 58th Annual Meeting, 2017)
The current study shows how brain sensing can offer insight to the evaluation of human spatial orientation in virtual reality (VR) and establish a role for electroencephalography (EEG) in virtual navigation. Research suggests that the evaluation of spatial orientation in VR benefits by going beyond performance measures or questionnaires to measurements of the user’s cognitive and neurophysiological state. While EEG has emerged as a practical brain sensing technology in cognition research, spatial orientation tasks often rely on which reference frame participants used, their ability to update head rotation, and/or left-right confusion which may be inaccessible to this measurement. EEG has been shown to correlate with human spatial orientation in previous research. In this paper, we use convolutional neural network (CNN), an advanced technique in machine learning, to train a detection model that can identify moments in which VR users gain some increase in spatial orientation demands. Our results demonstrate that we can indeed use machine learning to detect such cognitive states as spatial orientation demanding in virtual reality research with 96% accuracy on average.
Keywords: NSERC DG 2026; Riecke; Riecke_2017; bernhard-riecke; point-to-orig; point-to-origin; poster; posterWithoutPaper; spatial updating; talkWithoutPaper; thinh-nguyen-vo